Silver(I) and zinc(II) complexes with symmetrical cinnamaldehyde Schiff base derivative: Spectroscopic, powder diffraction characterization, and antimycobacterial studies. (15th May 2018) - Amaral, Thaeny C.; Miguel, Fábio B.; Couri, Mara R.C.; Corbi, Pedro P.; Carvalho, Marcos A.; Campos, Débora L.; Pavan, Fernando R.; Cuin, Alexandre
Graphical abstract: Silver(I) and zinc(II) complexes of the Schiff base – N, N ′-bis( trans- cinnamaldehyde) ethane-1, 2-diamine (EnCinn) were synthesized. Biological studies were evaluated against Mycobacterium tuberculosis and the silver(I) compounds have been shown potent activity action as commercial Silver Sulfadiazine complex (SSD). Spectroscopic and analytical characterization were performed to complexes and crystal structures of the two complexes were achieved using Powder Diffraction state-of-art . Abstract: Silver(I) and zinc(II) complexes with N, N ′-bis( trans- cinnamaldehyde)ethane-1, 2-diamine (EnCinn) have been synthesized and characterized by elemental analysis, simultaneous thermogravimetric and differential thermal studies (TG-DTA), infrared (IR), 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopic measurements and electrospray ionization quadrupole time-of-flight mass spectrometry (ESI-QTOF-MS). Crystal and molecular structure descriptions were performed based on powder X-ray diffraction data. The AgEnCinn complex has a polymeric structure where the ligand bridges between two Ag(I) ions, while the ZnEnCinn complex has a monomeric structure with EnCinn acting as chelating ligand. Antimycobacterial assays over Mycobacterium tuberculosis showed the activity of the Ag(I) complex with Minimum Inhibitory Concentration (MIC) value of 22.7 μmol L −1, while the Zn(II) complex was shown to be inactive over the same experimental conditions.